Pulsed Radiofrequency of the Trigeminal Ganglion for Treating Postherpetic Neuralgia of the Ophthalmic Branch - Liu, Dong-Yang (Pain Res Manag, 2021)
Postherpetic neuralgia (PHN) is a painful, long-lasting condition as a consequence of nerve damage resulting from a herpes zoster infection. Although there are many different treatments available to reduce pain duration and severity, PHN is often refractory to them and no single therapy shows an effective cure for all cases of PHN, especially for those involving the ophthalmic branch of the trigeminal nerve. Pulsed radiofrequency (PRF) is a minimally invasive procedure for pain treatment that has been practiced over the past decade. However, its clinical efficacy and safety for treating PHN involving the ophthalmic branch of the trigeminal nerve have not been evaluated. Objective. This study aimed to evaluate the efficacy and safety of PRF for treating PHN involving the ophthalmic branch of the trigeminal ganglion. Study Design. An observational study. Setting. All patients received PRF of the ophthalmic branch of the trigeminal nerve, pain intensity was assessed by a visual analogue scale (VAS), and complications before and after PRF stimulation were noted. Methods. Thirty-two patients with PHN of the ophthalmic branch were treated by PRF of the ophthalmic branch with controlled temperature at 42°C for 8 min. Pain relief, corneal reflex, sleep quality, and satisfaction were assessed for all patients. Results. Thirty out of 32 patients (93.75%) reported significant pain reduction after PRF treatment. Twenty-eight of them (87.5%) were satisfied with their sleep and obtained a pain score lower than 3 following the procedure. Only two patients had a recurrence of the severe burning pain and returned to the hospital for other medical therapies 2 weeks after the PRF procedure. No patient lost the corneal reflex. Limitations. This study is an observational study and a nonprospective trial with a short-term follow-up period. Conclusion. PRF of the trigeminal ganglion of the ophthalmic branch can significantly reduce pain sensation and improve sleep quality and satisfaction for PHN of the ophthalmic branch.